2005
DOI: 10.1159/000086487
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Myosin Light Chain Kinase mRNA Is Related to Metastasis in Non-Small Cell Lung Cancer

Abstract: Background: The invasiveness of tumor cells depends in large part on their motility, which in turn depends on cytoskeletal function. A major cytoskeletal component involved in cell motility is myosin II, the classical form of myosin first identified in muscle but also expressed in nonmuscle cells. Myosin II is activated by myosin light chain kinase (MLCK), which phosphorylates it on its regulatory light chain. In this context, the contribution made by MLCK to tumor cell motility and invasiveness has been inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…However, there is still a profound lack of understanding of the exact mechanical roles of myosin IIA during cell migration. A recent clinical study of patients with NSCLC found a significant positive correlation between the expression levels of myosin light chain kinase (which activates myosin II) and the likelihood of disease recurrence and metastasis (Minamiya et al, 2005), indicating that myosin IIA activation could be a factor contributing to metastasis. A key role for myosin IIA in cancer cell metastasis has been further suggested, indirectly, by a number of published studies focusing on the small calcium-binding protein, metastasin-1.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still a profound lack of understanding of the exact mechanical roles of myosin IIA during cell migration. A recent clinical study of patients with NSCLC found a significant positive correlation between the expression levels of myosin light chain kinase (which activates myosin II) and the likelihood of disease recurrence and metastasis (Minamiya et al, 2005), indicating that myosin IIA activation could be a factor contributing to metastasis. A key role for myosin IIA in cancer cell metastasis has been further suggested, indirectly, by a number of published studies focusing on the small calcium-binding protein, metastasin-1.…”
Section: Discussionmentioning
confidence: 99%
“…ROCK and MLCK have been shown to play distinct but complementary roles in the regulation of MLC phosphorylation, actin structures and motility of cells in 2D tissue culture conditions [107][108][109][110]. Elevated MLCK expression has been detected in numerous tumour types [111][112][113][114] and cancer cell lines [115][116][117] suggesting that increased MLCK activity resulting from overexpression or increased calcium transients might act to drive cancer cell motility in vivo, possibly in co-operation with ROCK. ZIPK has recently been shown to be phosphorylated and activated by ROCK [118], and can phosphorylate common substrates including MLC [45], MYPT1 [119] and CPI-17 [68].…”
Section: Actin Organisation In Complex Environmentsmentioning
confidence: 99%
“…High levels of the myosin kinase Rho-associated protein kinase 1 (ROCK1) are associated with poor survival in breast cancer patients (Lane et al, 2008) and correlate with poor tumour differentiation, muscle invasion and lymph node metastasis in bladder cancer (Kamai et al, 2003). One clinical study showed a positive correlation between myosin light chain kinase, which activates myosin II, with disease recurrence and metastasis in non-small cell lung cancer (Minamiya et al, 2005). Better reagents for the detection of active myosin II or specific enrichment of myosin II isoforms are needed for further clinical studies (Vicente-Manzanares et al, 2009).…”
Section: Cortexmentioning
confidence: 99%
“…Aberrant association of filamin-A with the prion protein PrPA correlates with worse prognosis in pancreatic cancer. A secreted variant of filamin-A in the blood correlates with highgrade astrocytomas and metastatic breast cancer (Ai et al, 2011;Alper et al, 2009;Anilkumar et al, 2003;Bedolla et al, 2009;Burton et al, 2010;Castoria et al, 2011;Kwon et al, 2008;Li et al, 2010b;Li et al, 2010c;Li et al, 2009;Loy et al, 2003;Smith et al, 2007;Sy et al, 2010;Uramoto et al, 2010;Zhou et al, 2011) Formins (Minamiya et al, 2005;Oslejskova et al, 2008) T-plastin (T-fimbrin) Microvilli of epithelial and mesenchymal cells Crosslinks F-actin into straight bundles T-plastin expression is enhanced in cisplatin-resistant human cancer cell lines (Hisano et al, 1996) L-plastin Crosslinks actin into orthogonal networks by forming tetramers. Forms a scaffold for signalling complexes and keeps SMAD3 or SMAD4 inhibited.…”
mentioning
confidence: 99%